Pluralidad de concepciones en el pensamiento geográfico actual - López Trigal, Lorenzo (Estudios humanísticos. Geografía, historia y arte, 1991)
A synthesis is offered of the changes that have taken place in Geography in the second half of this century - and innovative period of greater complexity for this discipline, which really appears as «new» as opposed to the «tradition», or earlier classic position. New tendencies, with afaster diffusion in the Anglo-Saxon schools of geography than in the others, were to follow, one after the other, from the fifties onwards ¿ those known as quantitative, theoretical, humanistic and radical are the best known and most relevant - However, following a lively and highly critical debate about each of these tendencies in previous years, there is now greater consensus and inter-relationship between them.